Is mindfulness a part of the mental capacity in high-level Norwegian individual sport athletes?: An interview study about high-level ultra-distance triathlon athletes self-regulation during training and competition - Gjerdingen, J. (2013)
The difference between success and failure has become increasingly smaller in sport (Birrer & Morgan, 2010). While sport psychology relied mainly on "second wave" cognitive-behavioural interventions for the last four decades, a new direction has recently been suggested. A "third wave" approach in sport psychology, including mindfulness, assumes that ideal performance is a state that is not based on self-control or change in behaviour, but rather a state that arises from recognition and acceptance of thoughts, emotions and bodily sensations (Gardner & Moore, 2004). Experiencing being in the moment, here and now, free from any form for evaluation. Aim of the study: This research project investigated how elite-level triathletes use aspects of mindfulness in training and competition (e.g. Thienot et al., 2012b) such as meta-awareness, acceptance and refocusing strategies. Mindfulness in sports is a recent field and the contemporary tenets need to be tested for validity. This study assessed whether a mindfulness approach is in line with athletes` practice, and tested how suitable a mindfulness definition may be suitable for sport.